Analisis Penerapan Profil Pelajar Pancasila dalam Penguatan Karakter Mandiri Siswa Kelas IV SD di Sekolah Kak Seto - Feronika Manalu; Deti Rostika; Yayang Furi Furnamasari (Jurnal Pendidikan Indonesia (JOUPI), 2023)
The study aims to describe how the application of the Pancasila student profile in strengthening the independent character of students and the strategies used by teachers to strengthen the independent character of students through the Pancasila student profile in grade IV elementary school students. This research is a qualitative type of research using qualitative descriptive analysis methods. The data collection techniques used are interviews, documentation, and questionnaires using research instruments, interview guidelines, and questionnaire sheets. The participants of the study were grade IV teachers and grade IV elementary school students at Kak Seto School, South Tangerang City. The results showed that the application of the Pancasila student profile in strengthening the independent character of grade IV elementary school students through habituation, extracurricular activities, and P5 activities. The strategy applied is the strategy of providing space and opportunities for students to develop and the strategy of building personal closeness to students. Based on the results of the study, the application of the Pancasila student profile carried out by teachers has succeeded in fostering the independence of grade IV elementary school students at Kak Seto School who have begun to act more independently.